2006
DOI: 10.1029/2005gc001115
|View full text |Cite
|
Sign up to set email alerts
|

Tracking the extent of the South Pacific Convergence Zone since the early 1600s

Abstract: [1] The South Pacific Convergence Zone (SPCZ) is the largest and most persistent spur of the Intertropical Convergence Zone. At the southeastern edge of the SPCZ near 170°W and 15°-20°S a surface ocean salinity frontal zone exists that separates fresher Western Pacific Warm Pool water from saltier and cooler waters in the east. This salinity front is known to shift east and west with the phase of the El Niño Southern Oscillation. We have generated subannually resolved and replicated coral oxygen isotopic time … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
153
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 132 publications
(163 citation statements)
references
References 43 publications
(117 reference statements)
10
153
0
Order By: Relevance
“…Our estimates of a reduction in mean SST by 3.5 °C relative to today, using our seasonal Tahiti coral Sr/Ca-SST relationship or by only 2.4 °C, using a possibly more suitable relationship for mean Indo-Pacific SST changes 32 , however, have relatively large uncertainties. As commonly observed at various locations 27,28,33 , between-colony offsets in mean Sr/Ca are evident among the modern Tahiti corals (Supplementary Methods and Supplementary Fig. S9).…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…Our estimates of a reduction in mean SST by 3.5 °C relative to today, using our seasonal Tahiti coral Sr/Ca-SST relationship or by only 2.4 °C, using a possibly more suitable relationship for mean Indo-Pacific SST changes 32 , however, have relatively large uncertainties. As commonly observed at various locations 27,28,33 , between-colony offsets in mean Sr/Ca are evident among the modern Tahiti corals (Supplementary Methods and Supplementary Fig. S9).…”
Section: Discussionsupporting
confidence: 66%
“…S9). The Sr/Ca ratios in coral skeletons are an established proxy for SST variability 10,11,[25][26][27][28] . Here we present a monthly resolved Sr/Ca-based SST reconstruction for a time window of 22 years generated from our HS1 coral (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The coral d 18 O range of 0.8% is close to that expected for annual SST cycle of 4°C, and thus we assume that coral d 18 O signal is mainly modulated by SST [Linsley et al, 2006], with additional effect of water d 18 O determined by a balance between precipitation and evaporation [Iijima et al, 2005] or by river discharge [Gagan et al, 1998]. As we assign the heavy and light peaks of d 18 O to the lowest and highest SST peaks (August and April), low-and high-density bands correspond to low and high SST seasons, respectively, which matches with the previous studies [Lough and Barnes, 1997].…”
Section: Age Modelsupporting
confidence: 66%
“…However, recently published coral Sr / Ca records covering the past hundreds of years indicate specific problems with the Sr / Ca thermometer, particularly on decadal to secular time scales (e.g. Linsley et al, 2004Linsley et al, , 2006Quinn et al 2006). Pfeiffer et al (2009) showed that the intrinsic variance of the singlecore Sr / Ca time series differs from core to core, limiting their use for absolute estimates of past temperature variations.…”
Section: A Grove Et Al: Spatial Linkages Between Coral Proxies Omentioning
confidence: 99%